1981
DOI: 10.1073/pnas.78.12.7742
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of murine muscular dystrophy with the proteinase inhibitor leupeptin.

Abstract: Mice with genetic muscular dystrophy were treated with intraperitoneal injections of the proteinase inhibitor leupeptin, beginning before the onset of weakness. A significant number of the treated animals failed to develop histological evidence ofdystrophy, compared with controls. Leupeptin treatment prevented (or delayed) the onset of muscular dystrophy in this experiment. In muscular dystrophy, there is biochemical and morphological evidence of abnormality of the muscle cell plasma membrane (1-3). Such defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Similarly, diversity studies and phylogenetic analysis have been reported for members of the family Secoviridae , including nepoviruses [ 45 , 51 ]. However, several new nepoviruses have been characterized recently, and the number of complete genome sequences of nepovirus isolates has increased exponentially in the past five years [ 1 , 2 , 4 , 12 , 15 , 18 , 23 25 , 41 , 50 , 55 , 56 , 58 ]. In this study, we built on these latest advancements in nepovirus research and carried out metagenomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, diversity studies and phylogenetic analysis have been reported for members of the family Secoviridae , including nepoviruses [ 45 , 51 ]. However, several new nepoviruses have been characterized recently, and the number of complete genome sequences of nepovirus isolates has increased exponentially in the past five years [ 1 , 2 , 4 , 12 , 15 , 18 , 23 25 , 41 , 50 , 55 , 56 , 58 ]. In this study, we built on these latest advancements in nepovirus research and carried out metagenomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Other important functions for this cysteine proteinase are its potential involvement in the processing of proinsulin (Docherty et al 1983) and other hormones, including endorphin (Suhar and Marks 1979) and proenkephalin (Marks et al 1986). Cathepsin B is also implicated in muscular dystrophy (Sher et al 1981;Stracher et al 1978).…”
Section: Introductionmentioning
confidence: 99%
“…1A ) is a secondary metabolite produced by actinomycetes ( 3 6 ), which has broad-spectrum protease-inhibitory activities, including serine, cysteine, and threonine proteases ( 7 11 ). Leupeptin treatment can prevent or delay muscular dystrophy in mouse or chicken models ( 12 ). Rabbits treated with leupeptin did not develop experimental autoimmune myasthenia gravis despite repeated acetylcholine receptor injections ( 13 ).…”
Section: Introductionmentioning
confidence: 99%